Ve1‐mediated resistance against Verticillium does not involve a hypersensitive response in Arabidopsis. (27th May 2013) - Zhang, Zhao; van Esse, H. Peter; van Damme, Mireille; Fradin, Emilie F.; Liu, Chun‐Ming; Thomma, Bart P. H. J.
Summary: The recognition of pathogen effectors by plant immune receptors leads to the activation of immune responses that often include a hypersensitive response (HR): rapid and localized host cell death surrounding the site of attempted pathogen ingress. We have demonstrated previously that the recognition of the Verticillium dahliae effector protein Ave1 by the tomato immune receptor Ve1 triggers an HR in tomato and tobacco. Furthermore, we have demonstrated that tomato Ve1 provides Verticillium resistance in Arabidopsis upon Ave1 recognition. In this study, we investigated whether the co‐expression of Ve1 and Ave1 in Arabidopsis results in an HR, which could facilitate a forward genetics screen. Surprisingly, we found that the co‐expression of Ve1 and Ave1 does not induce an HR in Arabidopsis. These results suggest that an HR may occur as a consequence of Ve1/Ave1‐induced immune signalling in tomato and tobacco, but is not absolutely required for Verticillium resistance.